Prazer! Reich! A base de uma educação livre - Oliveira, Fabrício Inácio de (2008)
A search based on the work of Reich and its connection with education. It was intended along the theoretical way by work of Reich to the evidence in relation with education were reached on a primary manner or, at least, with fewer interpretative filters. The understanding of the philosophical and political time of Europe in 1920 - 1951, mainly regarding the establishment and influence of Freudian thought, was very important to answer the question motivating the search: you may think the work of Reich as a basis epistemological to "another" education?